Genetic diversity and environmental influence on morphological and yield parameters of maize in Benin - EZIN, VINCENT; Kpanougo, Chabrolle M. I.; AHANCHEDE, ADAM (My University, 2022)
Seeds are the most important input in agricultural production and its quality seed determines the yield of the crop. They contribute to nearly 30% of crop productivity. The present study aims at surveying, collecting and characterizing maize accessions from the North, Centre and South Benin. Thirty-two (32) accessions were collected from 11 townships of Benin. Four experiments (Bassila, Glazoue, N'Dali and Adjohoun sites) were carried out to evaluate the agro-morphological characteristics of the collected 32 accessions. Eighteen (18) quantitative parameters were measured at each site. The accessions were classified into 3 groups by the hierarchical ascending classification showing a very important variability among cultivars with very highly significant (P < 0.001) or highly significant (P < 0.01) differences. The observed diversity among the different cultivars were based on plant height, growth life cycle, ear height, yield and yield components. The collection consisted of 18 intermediatematuring cultivars showing big corn size with the ears inserted at a great height (Group 1), 8 late-maturing cultivars with the best vegetative and reproductive traits (Group 2) and 6 early-maturing cultivars with the best reproductive growth and best ear and grain yields (Group 3). The phenotypic variability of the cultivars was more related to their agronomic and morphological traits than their origin. These diverse groups of accessions could be used to develop improved maize varieties with high yield potential and adapted to different agroclimatic conditions
Keywords: Maize; Evaluation; Survey-collection; Earliness; Diversity